Bolt tension monitoring with reusable fiber Bragg-grating sensors. (February 2016) - Khomenko, Anton; Koricho, Ermias G; Haq, Mahmoodul; Cloud, Gary L
Bolted/mechanical fastening is one of the oldest and most widely used joining techniques. While it has many advantages such as ease of assembly and repair, it also has some important limitations. One such concern is bolt clamping load control and monitoring during and after joint assembly. Conventionally used torque wrenches can provide only an approximation of the clamping load and cannot be used for load monitoring. Clamping force transducers are bulky, expensive, and cannot usually be incorporated into the bolted joint for continuous load monitoring in the field. In this work, a novel implementation of a transducer device, called here for convenience the "bolt tension monitor, " is described and tested. It utilizes removable and reusable fiber Bragg-grating sensor(s) embedded in a bolt shaft for preload and retained clamping force measurements. While the inherent small size of the fiber Bragg-grating provides precise monitoring without significant effect on the intrinsic properties of the bolt, the embedding of an fiber Bragg-grating sensor with temporary adhesives allows quick assembly, disassembly, and reassembly of the sensor. Furthermore, these instrumented bolts can be used for structural health monitoring and defect detection in joints and structures. The technique shows great potential in simple adaptation to conventional manufacturing practices, precise clamping load measurement, and structural health monitoring of bolts and resulting joints.